Assigning the task of lighting the fire to the Patil of the village - Mumbai Archive Project Team (Jio Institute, 2024)
The final rituals are performed by the senior member of the family. In the past, when only one bonfire was kindled in the entire village, the task of lighting the fire was assigned to the patil (village headman).